Live from Baghdad - Shanley, John Patrick 1950-; Sexton, Timothy J. 1959-; Keaton, Michael 1951-; Bonham Carter, Helena 1966-; Taylor, Lili 1967-; McGill, Bruce 1950-; Wisdom, Robert; Leonard, Joshua 1975-; Guilfoyle, Paul 1949-; Wiener, Robert; Wiener, Robert (HBO Video, 2003)
In 1990, CNN was a 24-hour news network in search of a 24-hour story. They were about to find it in Baghdad. Up against the three big networks, Wiener, a veteran producer, along with his longtime producing partner and their team of rebels with a cause, take the biggest risks to get the biggest stories - unlike their rivals - live at a moment's notice
Orig.: USA, 2002
Special features: Audio commentary with director Mick Jackson ; Cast and crew bios
Keywords: Fernsehfilm; Cable News Network / Drama; Persian Gulf War, 1991 / Journalists / Drama; Cable News Network; Journalists; 1991; DVD-Video discs; Feature films; Drama; Film; DVD-Video